Piano sonata no. 12 in A-flat major, op. 26 (Fourmage) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; Fourmage; France)
Edition of the Piano sonata no. 12 in A-flat major, op. 26, published by Fourmage in the middle of the nineteenth century.